2008
DOI: 10.1182/blood.v112.11.325.325
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemotherapy with Fludarabine (F), Cyclophosphamide (C), and Rituximab (R) (FCR) Versus Fludarabine and Cyclophosphamide (FC) Improves Response Rates and Progression-Free Survival (PFS) of Previously Untreated Patients (pts) with Advanced Chronic Lymphocytic Leukemia (CLL)

Abstract: Introduction: Previous phase II studies have suggested that a combination of FCR may increase the outcome of both untreated and relapsed CLL pts. In order to validate this concept the German CLL study group (GCLLSG) initiated a multicentre, multinational phase III trial, CLL8, to evaluate the efficacy and tolerability of FCR versus FC for the first-line treatment of pts with advanced CLL. Methods and Patients: 817 pts with good physical fitness as defined by a cumulative illness rating scale (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…Two recent, large randomized trials have demonstrated that chemoimmunotherapy results in superior response rates and progression-free survival over chemotherapy alone. 7,8 Alemtuzumab, a humanized immunoglobulin (Ig)G1 monoclonal antibody targeting the human CD52 antigen, has been approved for use in patients with CLL based on 2 clinical studies in patients with refractory disease and frontline patients, respectively. 9,10 Monoclonal antibodies directed against other target antigens have also demonstrated activity, most notably the anti-CD20-specific monoclonal antibody rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent, large randomized trials have demonstrated that chemoimmunotherapy results in superior response rates and progression-free survival over chemotherapy alone. 7,8 Alemtuzumab, a humanized immunoglobulin (Ig)G1 monoclonal antibody targeting the human CD52 antigen, has been approved for use in patients with CLL based on 2 clinical studies in patients with refractory disease and frontline patients, respectively. 9,10 Monoclonal antibodies directed against other target antigens have also demonstrated activity, most notably the anti-CD20-specific monoclonal antibody rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…30 An important multicenter phase III trial demonstrating a significant advantage of progression-free survival achieved by adding RTX to the initial chemotherapy reg-imen in treatment-naive CLL patients found no significant benefit for RTX in the group of advanced-disease patients (Binnet stage C). 31 This recent observation suggests that hitherto poorly understood factors (possibly complement abnormalities common in advancedstage CLL) 17 may be responsible for this lack of clinical effect. If proven efficacious in a larger group of CLL patients, adding FFP may represent an additional, nontoxic and cost-effective way of increasing the efficacy of RTX, thus facilitating its use in patients with malignant B-cell diseases in combination with chemotherapy as well as in nonmalignant autoimmune diseases, such as cryoglobulinemia, 32 Sjogren's syndrome, 33 and other conditions.…”
Section: Future Directionsmentioning
confidence: 99%
“…Alemtuzumab, 15 bendamustine, 16 ofatumumab, 17 and rituximab have all received US Food and Drug Administration (FDA) approval for treatment of CLL in the last decade, which has also seen better definition of the role of allogeneic transplant for selected patients. 18 Multidrug regimens combining chemotherapeutic agents with monoclonal antibodies have dramatically improved response rates, progression free survival, [19][20][21] and overall survival (OS). 22 There have also been considerable improvements in the understanding and management of complications of CLL including autoimmune hemolytic anemia (AIHA), immune thrombocytopenic purpura (ITP), pure red blood cell aplasia (PRBCA), hypogammaglobulinemia, and infectious complications.…”
Section: Introductionmentioning
confidence: 99%